Unidirectional magnetoelectric-field multiresonant tunneling. (9th January 2015) - Kamenetskii, E O; Hollander, E; Joffe, R; Shavit, R
Abstract: Unidirectional multi-resonant tunneling of the magnetoelectric (ME) field excitations through a subwavelength (regarding the scales of regular electromagnetic radiation) vacuum or isotropic-dielectric regions has been observed in two-port microwave structures having a quasi-2D ferrite disk with magnetic dipolar mode (MDM) oscillations. The excitations manifest themselves as Fano-resonance peaks in the scattering-matrix parameters at the stationary states of the MDM spectrum. The ME near-field excitations are quasimagnetostatic fields with non-zero helicity parameter: Topological phase properties of ME fields are determined by edge chiral currents of MDM oscillations. We show that while for a given direction of a bias magnetic field (in other words, for a given direction of time), the ME field excitations are considered as 'forward' tunneling processes, in the opposite direction of a bias magnetic field (the opposite direction of time), there are 'backward' tunneling processes. Unidirectional ME field resonant tunneling is observed due to the distinguishable topology of the 'forward' and 'backward' ME field excitations. We establish a close connection between the Fano-resonance unidirectional tunneling and the topology of the ME fields in different microwave structures.